PERBANDINGAN SIFAT KIMIA DAN SENSORIS HASIL PENYANGRAIAN KOPI (Coffea sp) DARI PENGGUNAAN 3 BAHAN ALAT SANGRAI YANG BERBEDA - Gae Lada, Yulius; Taime, Janet L.; Condro, Novita; Mangaluk, Efraim (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
This research aims to compare the chemical and sensory properties of coffee roasting results from the use of three different roasting materials. This research was carried out at the Biological Laboratory of Ottow Geissler University Papua and the Jayapura Health Polytechnic General Laboratory for ± 2 months, namely May – June. The method used in this research is an experimental method with a batch system. To analyze the chemical properties resulting from roasting coffee using three different roasting materials, it is described from laboratory data. Meanwhile, for the analysis of sensory properties, a completely randomized design (CRD) was used with 3 treatments, namely the use of roasting containers made of aluminum, iron and clay. The results of the research showed that coffee roasting using 3 different roasting materials had different average pH values ??and titration acidity values, namely pH values ??of 5.0 for aluminum containers, 4.5 for iron containers and 4.1 for clay containers and titration acidity values ??of 0.053% (aluminium), 0.08% (iron) and 0.08% (clay). Meanwhile, in the sensory (organoleptic) properties test, the treatment with the best score was ground coffee produced using a clay roaster with a sharper aroma in ground coffee and brewed coffee and an even sour taste.